Why prison? - Scott, David Gordon (Cambridge : Cambridge University Press, 2013)
Prison studies has experienced a period of great creativity in recent years, and this collection draws together some of the field's most exciting and innovative contemporary critical writers in order to engage directly with one of the most profound questions in penology - why prison? In addressing this question, the authors connect contemporary penological thought with an enquiry that has received the attention of some of the greatest thinkers on punishment in the past. Through critical exploration of the theories, policies and practices of imprisonment, the authors analyse why prison persists and why prisoner populations are rapidly rising in many countries. Collectively, the chapters provide not only a sophisticated diagnosis and critique of global hyper-incarceration but also suggest principles and strategies that could be adopted to radically reduce our reliance upon imprisonment. -- Publisher website.
Why prison? : posing the question / David Scott -- Prisons and social structure in late-capitalist societies / Alessandro De Giorgi -- The prison paradox in neoliberal britain / Emma Bell -- Crafting the neoliberal state: workfare, prisonfare, and social insecurity / Loic Wacquant -- Pleasure, punishment and the professional middle class / Magnus Hornqvist -- Penal spectatorship and the culture of punishment / Michelle Brown -- Prison and the public sphere: toward a democratic theory of penal order / Vanessa Barker -- The iron cage of prison studies / Mark Brown -- The prison and national identity : citizenship, punishment and the sovereign state / Emma Kaufman and Mary Bosworth -- Punishing the detritus and the damned : penal and semi-penal institutions in liverpool / Vickie Cooper and Joe Sim -- Why prison? : incarceration and the great recession / Keally McBride -- Ghosts of the past, present, and future of penal reform in the United States / Marie Gottschalk -- Schooling the carceral state: challenging the school to prison pipeline / Erica Meiners -- Why no prisons? / Julia C. Oparah -- Unequalled in pain / David Scott.
Includes bibliographical references (pages 325-369) and index.
Keywords: Prisons; Punishment; Crime; Criminal justice, Administration of